Studi Kasus Cystitis pada Anjing Skye di Klinik Hewan Raja Petshop Surabaya: Cystitis pada anjing skye di klinik hewan raja petshop surabaya - Kalego, Alfred Ade Putra (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2023)
On May 18, 2023, Mrs. Florensi had brought her dog Skye for a routine check-up. Anamnesis had been conducted for Skye, and the results indicated that Skye's appetite and drinking habits were normal. However, according to Mrs. Florensi, Skye had been urinating frequently in small amounts and There had been drops of blood on the pee pad, Leading her to believe that Skye had been in heat for an extended period. Upon palpation, the urinary bladder had felt hard, Prompting further examinations such as X-rays, urinalysis, and a vaginal swab to be conducted. The cytology results of the vaginal swab had shown the presence of red blood cells and bacterial colonies. Additionally, a significant number of parabasal and intermediate cells had been observed (indicating anestrus) rather than being in heat. The urinalysis had revealed leukocytes (+3), nitrites (+) indicating infection and inflammation in the urinary tract, protein (+2), microalbumin (+3), and creatinine (+1) indicating kidney filtration damage, vitamin C (+1) due to excessive vitamin administration, specific gravity of urine 1.030 (indicating concentrated urine), ketones (-), blood (-) normal, urobilinogen and bilirubin (-) indicating no liver disorders, pH 6.5 normal, and calcium (-). The lateral X-ray results showed no formation of urinary crystals in the urinary bladder but revealed urine accumulation. Based on the anamnesis, clinical symptoms, physical examination, and supporting tests, Skye's condition had indicated Cystitis.